1 answer:
Answer:
Step-by-step explanation:
6) y = 2x² + 6x - 80
1) y = 2*x² + 2*3x - 2*40
y = 2 [ x² + 3x - 40]
2) Sum = 3
Product = -40
Factors = (-5) ; 8 {-5 +8 = 3 ; (-5)*8 = -40}
y = 2 [ x² + 8x - 5x - 40]
= 2 [ x(x + 8) - 5(x + 8) ]
= 2 [ (x +8) (x - 5)]
y = 2(x +8)(x -5)
b) y = 0
2(x + 8)(X - 5) = 0
x + 8 = 0 ; x - 5 = 0
x = -8 ; x = 5
(-8) ; 5 are the zeros.
You might be interested in
Negative 3 and 0,6 hope you do good on future problems
Answer:
<h2>
all <u>
a,d, and e</u>
are correct. Use the area of a circle formula to solve</h2>
Answer:
OK with what
Step-by-step explanation:
OK with what
Answer:
-83
Step-by-step explanation:
so plug in 10 in 8x. So it is 10*-8 -3.
-80-3=-83